Positive electrode composite material, preparation method thereof, positive electrode and lithium ion secondary battery
By introducing a cladding layer of lithium boron oxide and fluoride into the positive electrode material of lithium ion secondary battery, the problems of poor circulation performance and fast impedance growth of positive electrode materials in lithium ion secondary battery in the prior art are solved, and the problem of poor circulation performance and fast impedance growth in the lithium ion secondary battery in the prior art is achieved. Higher battery efficiency and lower impedance growth.
Patent Information
- Application Number
- CN202310944677.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-02-14
AI Technical Summary
The cathode materials in the prior art are difficult to effectively improve the circulation and impedance growth of lithium-ion secondary batteries.
Using a positive electrode composite material, the material comprises a high nickel positive electrode material, a lithium boron oxide covering a portion of its surface and a fluoride present in a dot-like form on the other portion of the surface, the composite material is achieved by washing and sintering processes. preparation.
The residual lithium amount is effectively reduced, the side reaction between the positive electrode composite material and the electrolyte is suppressed, the first Coulomb efficiency of the lithium-ion secondary battery is improved, the cycle performance is improved, and the impedance growth is reduced.
Smart Images

Figure CN119447200A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium ion secondary batteries, and in particular to a positive electrode composite material, a method for preparing the positive electrode composite material, and a positive electrode and a lithium ion secondary battery comprising the positive electrode composite material. Background Art
[0002] In recent years, with the continuous development of electronic technology, people's demand for battery devices used to support the energy supply of electronic devices has also been increasing. Nowadays, batteries that can store more electricity and output high power are needed. Traditional lead-acid batteries and nickel-metal hydride batteries can no longer meet the needs of new electronic products such as mobile devices such as smartphones and fixed devices such as power storage systems. Therefore, lithium-ion batteries have attracted widespread attention. In the process of developing lithium-ion batteries, their capacity and performance have been effectively improved.
[0003] Lithium-ion secondary batteries include a positive electrode containing positive electrode materials, a negative electrode, and an electrolyte. The configuration of the positive electrode material has a great influence on the performance of the lithium-ion secondary battery. Various studies have been conducted on the configuration of the positive electrode material. The high content of residual alkali (LiOH and Li2CO3) on the surface of the high-nickel positive electrode material leads to poor processing performance; residual lithium will cause the battery to produce gas, and the more residual lithium, the more serious the gas production; therefore, reducing the amount of residual lithium on the surface of the high-nickel positive electrode material has become the focus of current research. The existing technology is to reduce the residual lithium on the surface of the high-nickel positive electrode material by water washing modification, and the residual lithium will be greatly reduced, but at the same time, NiO-like substances will be generated on the surface of the material, resulting in increased impedance, and lattice lithium will be precipitated, resulting in unstable structure of the material and significantly deteriorated cycle performance.
[0004] The positive electrode materials in the prior art cannot effectively improve the cycle and impedance growth of lithium ion secondary batteries. Therefore, it is necessary to develop a new positive electrode composite material, a method for preparing the positive electrode composite material, and a positive electrode and a lithium ion secondary battery containing the positive electrode composite material. Summary of the invention
[0005] The main purpose of the present invention is to provide a positive electrode composite material, a method for preparing the positive electrode composite material, and a positive electrode and a lithium ion secondary battery comprising the positive electrode composite material, so as to solve the problem that the positive electrode materials in the prior art are difficult to effectively improve the cycle and impedance growth of lithium ion secondary batteries.
[0006] In order to achieve the above-mentioned object, according to one aspect of the present invention, there is provided a positive electrode composite material, which comprises: a high-nickel positive electrode material; lithium boron oxide coating a portion of the surface of the high-nickel positive electrode material; and fluoride present in a dotted form on another portion of the surface of the high-nickel positive electrode material, wherein the residual lithium content on the surface of the positive electrode composite material is less than 0.3wt%.
[0007] Furthermore, in the above-mentioned positive electrode composite material, lithium boron oxide uniformly covers the surface of the secondary particles and the grain boundaries of the primary particles of the high-nickel positive electrode material.
[0008] Furthermore, in the above-mentioned positive electrode composite material, the lithium boron oxide comprises one or more of LiBO2, Li3BO3, Li2B4O7, Li2B2O4 and Li3B3O6.
[0009] Furthermore, in the above-mentioned positive electrode composite material, the fluoride includes LiF.
[0010] Furthermore, in the above-mentioned positive electrode composite material, the fluoride also includes one or more of MgF2, AlF3, NH4F, MnF4, TiF3, ZrF4, SrF3 and MoF5.
[0011] Furthermore, in the above-mentioned positive electrode composite material, the high nickel positive electrode material has the general formula LiNi x Co y M 1-x-y O2, wherein 0.6≤x≤1, 0≤y<0.4, and M is one or more of Mn, Al, Mg, Ti, Fe, Cu, Zn, Ga, Zr, Mo, Nb and W.
[0012] Further, in the above positive electrode composite material, the amount of boron element in the positive electrode composite material is in the range of 0.01 wt % to 0.50 wt %.
[0013] Further, in the above positive electrode composite material, the amount of fluorine element in the positive electrode composite material is in the range of 0.01 wt % to 1.00 wt %.
[0014] According to another aspect of the present invention, a method for preparing a positive electrode composite material is provided, the method comprising: step S1: mixing a high-nickel positive electrode material with water or a solution formed by an acid and a non-aqueous solvent to obtain a first mixture; step S2: filtering the first mixture to obtain a filtered product, and then vacuum drying and grinding and sieving the filtered product to obtain a washed product; step S3: ball-milling the washed product with a boron-containing compound and a fluoride to obtain a second mixture; and step S4: sintering the second mixture to obtain the positive electrode composite material.
[0015] Further, in the above-mentioned method for preparing a positive electrode composite material, in step S1, the acid includes an organic acid, an inorganic acid or a mixture thereof, preferably, the organic acid includes one or more of maleic acid, acrylic acid, fumaric acid, malonic acid, oxalic acid, malic acid, glycolic acid, succinic acid, citric acid, trisaccharic acid and aconitic acid, preferably, the inorganic acid includes one or both of phosphoric acid and silicic acid.
[0016] Further, in the above method for preparing a positive electrode composite material, in step S1, the non-aqueous solvent includes an alcohol solvent, and preferably, the alcohol solvent includes one or more of methanol, ethanol, isopropanol, ethylene glycol and glycerol.
[0017] Further, in the above method for preparing a positive electrode composite material, in step S2, the vacuum drying is performed at a temperature in the range of 60°C-150°C, and the vacuum drying time is in the range of 0.1h-12h.
[0018] Further, in the above method for preparing a positive electrode composite material, in step S3, the rotation speed of ball milling is in the range of 100 rpm-500 rpm, and the time of ball milling is in the range of 10 min-2 h.
[0019] Further, in the above method for preparing a positive electrode composite material, in step S3, the fluoride comprises one or more of LiF, MgF2, AlF3, NH4F, MnF4, TiF3, ZrF4, SrF3 and MoF5.
[0020] Further, in the above method for preparing a positive electrode composite material, in step S3, the boron-containing compound comprises one or both of boric acid and boron oxide.
[0021] Furthermore, in the above method for preparing a positive electrode composite material, in step S4, the sintering temperature is in the range of 200°C-600°C, the sintering time is in the range of 2h-8h, preferably, the heating rate is in the range of 6°C / min-15°C / min, and preferably, the sintering atmosphere is oxygen.
[0022] According to another aspect of the present invention, a positive electrode for a lithium-ion secondary battery is provided. The positive electrode for a lithium-ion secondary battery comprises the positive electrode composite material described above.
[0023] According to another aspect of the present invention, a lithium ion secondary battery is provided. The lithium ion secondary battery includes: a positive electrode, a negative electrode, and a separator. The positive electrode includes the positive electrode composite material described above.
[0024] The positive electrode composite material, the method for preparing the positive electrode composite material, and the positive electrode and lithium ion secondary battery containing the positive electrode composite material of the present invention can effectively reduce the amount of residual lithium, inhibit the side reaction between the positive electrode composite material and the electrolyte in the lithium ion secondary battery, increase the first coulomb efficiency of the lithium ion secondary battery, improve the cycle performance of the lithium ion secondary battery and reduce the impedance growth of the lithium ion secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 A schematic structural diagram of a positive electrode composite material according to one embodiment of the present invention is shown.
[0026] Figure 2 A schematic diagram showing a method for preparing a positive electrode composite material according to one embodiment of the present invention is shown. DETAILED DESCRIPTION
[0027] It should be noted that, in the absence of conflict, the various embodiments and features in the embodiments in this application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments. The following embodiments are merely exemplary and are not intended to limit the scope of protection of the present invention.
[0028] As described in the background art, the positive electrode materials in the prior art are difficult to effectively improve the cycle and impedance growth of lithium-ion secondary batteries. In view of the problems in the prior art, a typical embodiment of the present invention provides a positive electrode composite material, which includes: a high-nickel positive electrode material; lithium boron oxide coating a portion of the surface of the high-nickel positive electrode material; and fluoride present in the form of dots on another portion of the surface of the high-nickel positive electrode material, and the residual lithium content on the surface of the positive electrode composite material is less than 0.3wt%. Figure 1 A schematic structural diagram of a positive electrode composite material according to one embodiment of the present invention is shown.
[0029] As the Ni content of high-nickel positive electrode materials increases, the capacity can be greatly improved, but the material has high residual alkali, high impedance, and poor cycle performance. The residual alkali on the surface of the material can be reduced by washing or acid washing, but the cycle improvement is small. By boron coating after washing, the impedance can be improved and the cycle performance can be further improved, but the reaction between the high-nickel positive electrode material and the electrolyte cannot be effectively suppressed, and the improvement in cycle performance and impedance growth is limited. Fluorine coating can inhibit the reaction between the high-nickel positive electrode material and the electrolyte, improve the cycle retention rate, and inhibit impedance growth, but agglomeration is easily generated during the fluorine coating process, and the initial impedance is higher than that of boron coating. By coating with boron and fluorine at the same time, the boron-containing compound is in a molten state during sintering, which helps the granular fluoride to be evenly dispersed on the surface of the high-nickel positive electrode material, thereby achieving the effect of reducing impedance and improving cycle retention rate.
[0030] Fluoride exists in the form of dots on another part of the surface of the high-nickel positive electrode material, which can retain more lithium ion channels. During the charge and discharge process of the lithium-ion secondary battery, the high-nickel positive electrode material is protected by the lithium boron oxide covering a part of the surface of the high-nickel positive electrode material and the fluoride existing in the form of dots on another part of the surface of the high-nickel positive electrode material, which prevents the high-nickel positive electrode material in the lithium-ion secondary battery from being corroded by the electrolyte, thereby showing lower impedance growth and good cycle performance.
[0031] In the positive electrode composite material of the present invention, by coating the lithium boron oxide on a part of the surface of the high-nickel positive electrode material, by the fluoride existing in the form of dots on another part of the surface of the high-nickel positive electrode material, and by washing treatment, the amount of residual lithium can be effectively reduced, the side reaction between the positive electrode composite material and the electrolyte in the lithium-ion secondary battery can be inhibited, the first coulomb efficiency of the lithium-ion secondary battery can be increased, the cycle performance of the lithium-ion secondary battery can be improved, and the impedance growth of the lithium-ion secondary battery can be reduced.
[0032] In some embodiments of the present invention, in order to more effectively improve the initial coulombic efficiency of the lithium ion secondary battery, more effectively improve the cycle performance of the lithium ion secondary battery and more effectively reduce the impedance growth of the lithium ion secondary battery, in the above-mentioned positive electrode composite material, lithium boron oxide is evenly covered on the surface of the secondary particles of the high nickel positive electrode material and on the grain boundaries of the primary particles. Uniform coverage means that the coating thickness of different regions is close. The secondary particles are agglomerates composed of primary particles.
[0033] In some embodiments of the present invention, in order to more effectively improve the first coulombic efficiency of lithium-ion secondary batteries, more effectively improve the cycle performance of lithium-ion secondary batteries and more effectively reduce the impedance growth of lithium-ion secondary batteries, in the above-mentioned positive electrode composite material, lithium boron oxide contains one or more of LiBO2, Li3BO3, Li2B4O7, Li2B2O4 and Li3B3O6.
[0034] In some embodiments of the present invention, in order to more effectively prevent the side reaction between the positive electrode composite material and the electrolyte in the lithium ion secondary battery, more effectively improve the cycle performance of the lithium ion secondary battery, and more effectively reduce the impedance growth of the lithium ion secondary battery, in the above-mentioned positive electrode composite material, the fluoride includes LiF. In some embodiments of the present invention, the fluoride mainly includes LiF.
[0035] In some embodiments of the present invention, in order to more effectively prevent the side reaction between the positive electrode composite material and the electrolyte in the lithium ion secondary battery, more effectively improve the cycle performance of the lithium ion secondary battery, and more effectively reduce the impedance growth of the lithium ion secondary battery, in the above-mentioned positive electrode composite material, the fluoride also includes one or more of MgF2, AlF3, NH4F, MnF4, TiF3, ZrF4, SrF3 and MoF5. Specifically, the fluoride may include a combination of one of MgF2, AlF3, NH4F, MnF4, TiF3, ZrF4, SrF3 and MoF5 and LiF; or the fluoride may include a combination of multiple of MgF2, AlF3, NH4F, MnF4, TiF3, ZrF4, SrF3 and MoF5 and LiF.
[0036] In some embodiments of the present invention, in the above-mentioned positive electrode composite material, the high nickel positive electrode material has the general formula LiNi x Co y M 1-x-y O2, wherein 0.6≤x≤1, 0≤y<0.4, and M is one or more of Mn, Al, Mg, Ti, Fe, Cu, Zn, Ga, Zr, Mo, Nb, and W. In some embodiments of the present invention, for example, a positive electrode precursor such as Ni x Co y Mn 1-x-y (OH)2 or Ni x Co y Al 1-x-y (OH)2 and lithium hydroxide sinter to form high nickel positive electrode materials such as LiNi x Co y Mn 1-x-y O2 or LiNi x Co y Al 1-x-y O2.
[0037] In some embodiments of the present invention, in the above-mentioned positive electrode composite material, the amount of boron in the positive electrode composite material is in the range of 0.01wt% to 0.50wt%. By controlling the amount of boron in the positive electrode composite material within the above-mentioned range, it is possible to ensure that lithium boron oxide is uniformly covered on a portion of the surface of the high-nickel positive electrode material, which can improve the first coulomb efficiency of the lithium ion secondary battery, improve the cycle performance of the lithium ion secondary battery and reduce the impedance growth of the lithium ion secondary battery.
[0038] Specifically, the amount of boron element in the positive electrode composite material can be in the following range: 0.01wt% to 0.50wt%, 0.01wt% to 0.45wt%, 0.01wt% to 0.40wt%, 0.01wt% to 0.35wt%, 0.01wt% to 0.30wt%, 0.01wt% to 0.25wt%, 0.01wt% to 0.20wt%, 0.01wt% to 0.15wt%, 0.01wt% to 0.10wt%, or 0.05wt% to 0.50wt%.
[0039] In some embodiments of the present invention, in the above-mentioned positive electrode composite material, the amount of fluorine in the positive electrode composite material is in the range of 0.01wt% to 1.00wt%. By controlling the amount of fluorine in the positive electrode composite material within the above-mentioned range, the side reaction between the positive electrode composite material and the electrolyte in the lithium ion secondary battery can be suppressed, the cycle performance of the lithium ion secondary battery can be improved, and the impedance growth of the lithium ion secondary battery can be reduced.
[0040] Specifically, the amount of fluorine element in the positive electrode composite material can be in the following range: 0.01wt% to 1.00wt%, 0.05wt% to 0.95wt%, 0.10wt% to 0.90wt%, 0.15wt% to 0.85wt%, 0.20wt% to 0.80wt%, 0.25wt% to 0.75wt%, 0.30wt% to 0.70wt%, 0.35wt% to 0.65wt%, 0.40wt% to 0.60wt%, 0.45wt% to 0.55wt% or 0.50wt% to 0.55wt%.
[0041] In another typical embodiment of the present invention, a method for preparing a positive electrode composite material is provided, the method comprising: step S1: mixing a high-nickel positive electrode material with water or a solution formed by an acid and a non-aqueous solvent to obtain a first mixture; step S2: filtering the first mixture to obtain a filtered product, and then vacuum drying and grinding and sieving the filtered product to obtain a washed product; step S3: ball-milling the washed product with a boron-containing compound and a fluoride to obtain a second mixture; and step S4: sintering the second mixture to obtain the positive electrode composite material. Figure 2 A schematic diagram showing a method for preparing a positive electrode composite material according to one embodiment of the present invention is shown.
[0042] The key technical point of the present invention is to wash with water or a solution formed by an acid and a non-aqueous solvent to remove the residual lithium on the surface of the high-nickel positive electrode material, and then dry and then sinter to coat lithium boron oxide and fluoride, so as to protect the substrate, thereby improving the cycle performance and inhibiting material degradation. The residual lithium on the surface of the high-nickel positive electrode material can be reduced by washing, and by coating a portion of the surface of the high-nickel positive electrode material with lithium boron oxide and having fluoride in the form of dots on another portion of the surface of the high-nickel positive electrode material, the side reaction between the positive electrode composite material and the electrolyte in the lithium-ion secondary battery can be inhibited, the first coulomb efficiency of the lithium-ion secondary battery is improved, the cycle performance of the lithium-ion secondary battery is improved, and the impedance growth of the lithium-ion secondary battery is reduced, and the boron and fluorine coating process is simple and the coating effect is good.
[0043] Through washing treatment and boron and fluorine coating treatment, the residual lithium on the surface of high-nickel positive electrode materials can be significantly reduced, the first coulomb efficiency can be increased, the cycle performance can be improved, the initial impedance and impedance growth can be reduced; the cycle retention rate of the material after boron and fluorine coating is improved, and the impedance is also significantly improved.
[0044] The lithium hydroxide and lithium carbonate on the surface of the high-nickel positive electrode material can be effectively removed through washing treatment; the coating amount of boron and fluorine is small, and as inert materials that react with the electrolyte, they can maintain stability under high voltage. After cycling, the high-nickel positive electrode material matrix is protected by the coating layer to prevent corrosion by the electrolyte, thereby showing lower impedance growth and good cycle performance.
[0045] In some embodiments of the present invention, in the above method for preparing a positive electrode composite material, in step S1, the acid includes an organic acid, an inorganic acid or a mixture thereof, preferably, the organic acid includes one or more of maleic acid, acrylic acid, fumaric acid, malonic acid, oxalic acid, malic acid, glycolic acid, succinic acid, citric acid, trisproitic acid and aconitic acid, preferably, the inorganic acid includes one or both of phosphoric acid and silicic acid. The above organic acid, inorganic acid or a mixture thereof can react well with the residual lithium on the surface of the high-nickel positive electrode material, can effectively reduce the residual lithium on the surface of the high-nickel positive electrode material, and can ensure a good washing effect.
[0046] In some embodiments of the present invention, in the above method for preparing a positive electrode composite material, in step S1, the non-aqueous solvent includes an alcohol solvent, preferably, the alcohol solvent includes one or more of methanol, ethanol, isopropanol, ethylene glycol and glycerol. The use of the above alcohol solvent can dissolve the acid, and the alcohol solvent itself does not have additional side reactions with the high-nickel positive electrode material, thereby suppressing the side reaction while effectively reducing the residual lithium on the surface of the high-nickel positive electrode material.
[0047] In some embodiments of the present invention, in order to effectively remove moisture from the material, in the above-mentioned method for preparing a positive electrode composite material, in step S2, the temperature for vacuum drying is in the range of 60°C-150°C, and the time for vacuum drying is in the range of 0.1h-12h. Preferably, the temperature for vacuum drying is in the range of 80°C-130°C, and the time for vacuum drying is in the range of 3h-9h. More preferably, the temperature for vacuum drying is in the range of 90°C-120°C, and the time for vacuum drying is in the range of 6h-8h.
[0048] In some embodiments of the present invention, in order to ensure that the washing product is evenly mixed with the boron-containing compound and the fluoride and to ensure a good mixing effect, in the above-mentioned method for preparing a positive electrode composite material, in step S3, the rotation speed of ball milling mixing is in the range of 100rpm-500rpm, and the time of ball milling mixing is in the range of 10min-2h. Preferably, the rotation speed of ball milling mixing is in the range of 200rpm-400rpm, and the time of ball milling mixing is in the range of 10min-1h. More preferably, the rotation speed of ball milling mixing is in the range of 300rpm-400rpm, and the time of ball milling mixing is in the range of 20min-40min.
[0049] In some embodiments of the present invention, in order to more effectively prevent the side reaction between the positive electrode composite material and the electrolyte in the lithium ion secondary battery, more effectively improve the cycle performance of the lithium ion secondary battery, and more effectively reduce the impedance growth of the lithium ion secondary battery, in the above method for preparing the positive electrode composite material, in step S3, the fluoride comprises one or more of LiF, MgF2, AlF3, NH4F, MnF4, TiF3, ZrF4, SrF3 and MoF5. When the fluoride comprises one or more of MgF2, AlF3, NH4F, MnF4, TiF3, ZrF4, SrF3 and MoF5 in step S3, the fluoride will undergo a substitution reaction with Li in the high-nickel positive electrode material to generate LiF, and therefore, the finally obtained positive electrode composite material comprises a combination of one or more of MgF2, AlF3, NH4F, MnF4, TiF3, ZrF4, SrF3 and MoF5 and LiF in a dotted form on the surface of another part of the high-nickel positive electrode material.
[0050] In some embodiments of the present invention, in order to more effectively improve the first coulombic efficiency of lithium-ion secondary batteries, more effectively improve the cycle performance of lithium-ion secondary batteries and more effectively reduce the impedance growth of lithium-ion secondary batteries, in the above-mentioned method for preparing a positive electrode composite material, in step S3, the boron-containing compound includes one or both of boric acid and boric oxide.
[0051] In some embodiments of the present invention, in the above method for preparing a positive electrode composite material, in step S4, the sintering temperature is in the range of 200°C-600°C, and the sintering time is in the range of 2h-8h. In some embodiments of the present invention, in the above method for preparing a positive electrode composite material, in step S4, the sintering temperature is in the range of 250°C-500°C, and the sintering time is in the range of 3h-7h. Preferably, the sintering temperature is in the range of 250°C-400°C, and the sintering time is in the range of 4h-6h. More preferably, the sintering temperature is in the range of 250°C-350°C, and the sintering time is in the range of 4h-5h. Most preferably, the sintering temperature is 300°C and the sintering time is 4h. In some embodiments of the present invention, in the above method for preparing a positive electrode composite material, in step S4, the heating rate is in the range of 6°C / min-15°C / min, preferably, the heating rate is in the range of 6°C / min-12°C / min, and more preferably, the heating rate is in the range of 8°C / min-10°C / min. In some embodiments of the present invention, in the above method for preparing a positive electrode composite material, in step S4, the sintering atmosphere is oxygen. By controlling the sintering temperature, sintering time and heating rate in step S4 within the above range, it can be ensured that the boron-containing compound is in a molten state during sintering, which helps to evenly disperse the granular fluoride on the surface of the high-nickel positive electrode material, thereby achieving the effect of reducing impedance and improving cycle retention rate.
[0052] In another typical embodiment of the present invention, a lithium ion secondary battery positive electrode is provided, and the lithium ion secondary battery positive electrode comprises the positive electrode composite material described above. Since the lithium ion secondary battery positive electrode of the present invention comprises the positive electrode composite material described above, it is possible to effectively reduce the amount of residual lithium, inhibit the side reaction between the positive electrode composite material and the electrolyte in the lithium ion secondary battery, improve the first coulomb efficiency of the lithium ion secondary battery, improve the cycle performance of the lithium ion secondary battery and reduce the impedance growth of the lithium ion secondary battery.
[0053] In another typical embodiment of the present invention, a lithium ion secondary battery is provided, the lithium ion secondary battery comprising: a positive electrode, a negative electrode, and a separator, the positive electrode comprising the positive electrode composite material described above. Since the lithium ion secondary battery of the present invention comprises the positive electrode composite material described above, it is possible to effectively reduce the amount of residual lithium, inhibit the side reaction between the positive electrode composite material and the electrolyte in the lithium ion secondary battery, improve the first coulomb efficiency of the lithium ion secondary battery, improve the cycle performance of the lithium ion secondary battery and reduce the impedance growth of the lithium ion secondary battery.
[0054] The positive electrode of the present invention includes a positive electrode collector and a positive electrode active material layer containing a positive electrode composite material. The positive electrode active material layer is formed on both surfaces of the positive electrode collector. A metal foil such as aluminum foil can be used as the positive electrode collector.
[0055] The negative electrode of the present invention includes a negative electrode current collector and a negative electrode active material layer containing a negative electrode active material. The negative electrode active material layer is formed on both surfaces of the negative electrode current collector. A metal foil such as copper (Cu) foil, nickel foil or stainless steel foil can be used as the negative electrode current collector.
[0056] The negative electrode active material layer contains one or more negative electrode materials capable of inserting and extracting lithium ions as negative electrode active materials, and may contain other materials, such as negative electrode binders and / or negative electrode conductors, if necessary. The negative electrode active material may be selected from one or more of lithium metal, lithium alloy, carbon material, silicon or tin and oxides thereof.
[0057] The separator of the present invention is used to separate the positive electrode and the negative electrode in the battery, and to allow lithium ions to pass therethrough while preventing a current short circuit caused by contact between the positive electrode and the negative electrode. The separator is, for example, a porous film formed of a synthetic resin or ceramic, and may be a laminated film in which two or more porous films are laminated. Examples of synthetic resins include, for example, polytetrafluoroethylene, polypropylene, polyethylene, and the like.
[0058] In an embodiment of the present invention, when the lithium ion secondary battery is charged, for example, lithium ions are extracted from the positive electrode and embedded in the negative electrode through the electrolyte impregnated in the separator. When the lithium ion secondary battery is discharged, for example, lithium ions are extracted from the negative electrode and embedded in the positive electrode through the electrolyte impregnated in the separator.
[0059] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0060] Example 1
[0061] Step S1: Weigh 100g of high nickel positive electrode material LiNi 0.95 Co 0.03 Mn 0.02 O2, add 100 g of water and stir for 1 h to obtain a mixed solution;
[0062] Step S2: Filter the mixed solution in step S1, put the filtered product into a vacuum drying oven and dry it at 120° C. for 8 h, grind and sieve to obtain a clean high-nickel positive electrode material;
[0063] Step S3: weigh 0.46 g of boric acid (H3BO3) and 0.15 g of AlF3, and mix them with the high-nickel positive electrode material in step S2 by ball milling to obtain a mixture, and the ball milling speed is 300 rpm and the time is 20 min;
[0064] Step S4: placing the mixture in step S3 into a tube furnace for sintering at a sintering temperature of 300° C., a sintering time of 4 hours, a heating rate of 10° C. / min, and an oxygen atmosphere; after the sample is cooled, grinding and sieving the sample to obtain a positive electrode composite material;
[0065] Step S5: 90 g of the positive electrode composite material prepared by the above process, 5 g of conductive carbon black as a conductive agent and 5 g of polyvinylidene fluoride (PVDF) as a binder are weighed to make an electrode sheet, and a button-type half-cell is made using the electrode sheet.
[0066] Example 2
[0067] A half-cell was prepared in the same manner as in Example 1, except that an ethanol solution having a maleic acid concentration of 3 wt % was used instead of water in step S1.
[0068] Example 3
[0069] A half-cell was prepared in the same manner as in Example 1, except that an ethanol solution having a phosphoric acid concentration of 2 wt % was used instead of water in step S1.
[0070] Example 4
[0071] A half-cell was prepared in the same manner as in Example 1, except that an isopropanol solution having a maleic acid concentration of 1.5 wt % and a silicic acid concentration of 1 wt % was used instead of water in step S1.
[0072] Example 5
[0073] A half-cell was prepared in the same manner as in Example 1, except that 0.26 g of boron oxide (B2O3) was used instead of 0.46 g of boric acid (H3BO3) in step S3, and the sintering temperature was 500°C in step S4.
[0074] Example 6
[0075] A half-cell was prepared in the same manner as in Example 1, except that 0.16 g MgF 2 was used instead of 0.15 g AlF 3 in step S3 .
[0076] Example 7
[0077] A half-cell was prepared by the same method as in Example 1, except that 0.91 g of boric acid (H3BO3) and 0.07 g of AlF3 were added in step S3.
[0078] Example 8
[0079] A half-cell was prepared by the same method as in Example 1, except that 0.23 g of boric acid (H3BO3) and 0.29 g of AlF3 were added in step S3.
[0080] Example 9
[0081] The half-cell was prepared in the same manner as in Example 1, except that the sintering temperature in step S4 was 600°C.
[0082] Example 10
[0083] The half-cell was prepared in the same manner as in Example 1, except that the sintering temperature in step S4 was 200°C.
[0084] Comparative Example 1
[0085] A half-cell was prepared in the same manner as in Example 1, except that in step S3 only 0.46 g of boric acid (H3BO3) was added, and no AlF3 was added.
[0086] Comparative Example 2
[0087] A half-cell was prepared in the same manner as in Example 1, except that only 0.15 g of AlF3 was added in step S3, and no boric acid (H3BO3) was added.
[0088] Comparative Example 3
[0089] A half-cell was prepared by the same method as in Example 1, except that step S3 and step S4 were omitted.
[0090] Comparative Example 4
[0091] Weigh 90g of high nickel cathode material LiNi 0.95 Co 0.03 Mn 0.02 O2, 5g of conductive carbon black as a conductive agent and 5g of polyvinylidene fluoride (PVDF) as a binder are made into an electrode sheet, and a button-type half-cell is made using the electrode sheet. The high-nickel positive electrode material is not processed by step S1, step S2, step S3 and step S4.
[0092] Battery performance test
[0093] The half-cells in Examples 1-10 and Comparative Examples 1-4 were subjected to charge and discharge tests and impedance tests at voltages between 2.0V and 4.25V. The half-cells in Examples 1-10 and Comparative Examples 1-4 were first subjected to a 0.1C charge and discharge cycle test at 25°C for one time, and then the first discharge capacity and initial impedance of the battery were tested. Then, a 1C charge and 5C discharge cycle test was performed at 60°C for 100 times to determine the capacity retention rate of the battery after 100 cycles, and then the post-cycle impedance was tested. Impedance growth rate = post-cycle impedance / initial impedance. First coulomb efficiency (%) = first discharge capacity / first charge capacity × 100%.
[0094] In addition, for the positive electrode materials prepared in the above-mentioned Examples 1-10 and Comparative Examples 1-4, a certain amount of positive electrode material powder was weighed, fully stirred in deionized water, and filtered to obtain a supernatant. The supernatant was titrated with a hydrochloric acid solution of a standard concentration to calculate the mass of lithium in the supernatant, and converted into the mass fraction of residual lithium in the positive electrode material. The experimental results are shown in Table 1 below.
[0095] Table 1 Electrochemical performance test results
[0096]
[0097] It can be seen from the above test results that the above embodiments of the present invention achieve the following technical effects:
[0098] By comparing the results of Examples 1-10 with Comparative Example 1, it can be seen that, compared with Comparative Example 1 in which no fluoride is present on the surface of the high-nickel positive electrode material, the battery in Examples 1-10 in which a portion of the surface of the high-nickel positive electrode material is coated with lithium boron oxide and another portion of the surface of the high-nickel positive electrode material has a higher first coulombic efficiency, a significantly higher capacity retention rate after 100 cycles, a significantly lower initial impedance, and a significantly lower impedance growth rate. In particular, by comparing Example 1 in which the conditions in steps S1-S2 and S4 are exactly the same with Comparative Example 1, it can be seen that, compared with Comparative Example 1 in which no fluoride is present on the surface of the high-nickel positive electrode material, the battery in Example 1 in which a portion of the surface of the high-nickel positive electrode material is coated with lithium boron oxide and another portion of the surface of the high-nickel positive electrode material has a higher first coulombic efficiency, a significantly higher capacity retention rate after 100 cycles, a significantly lower initial impedance, and a significantly lower impedance growth rate, and the positive electrode composite material in Example 1 has a lower residual lithium content.
[0099] By comparing the results of Examples 1-10 with Comparative Example 2, it can be seen that, compared with Comparative Example 2 in which there is no lithium boron oxide on the surface of the high nickel positive electrode material, the battery in Examples 1-10 in which a portion of the surface of the high nickel positive electrode material is coated with lithium boron oxide and another portion of the surface of the high nickel positive electrode material has a higher first coulombic efficiency, a significantly higher capacity retention rate after 100 cycles, a significantly lower initial impedance, and a significantly lower impedance growth rate. In particular, by comparing Example 1 in which the conditions in steps S1-S2 and S4 are exactly the same with Comparative Example 2, it can be seen that, compared with Comparative Example 2 in which there is no lithium boron oxide on the surface of the high nickel positive electrode material, the battery in Example 1 in which a portion of the surface of the high nickel positive electrode material is coated with lithium boron oxide and another portion of the surface of the high nickel positive electrode material has a higher first coulombic efficiency, a significantly higher capacity retention rate after 100 cycles, a significantly lower initial impedance, and a significantly lower impedance growth rate, and the positive electrode composite material in Example 1 has a lower residual lithium content.
[0100] By comparing the results of Examples 1-10 with Comparative Example 3, it can be seen that, compared with Comparative Example 3 in which there is no lithium boron oxide and fluoride on the surface of the high nickel positive electrode material, the battery in Examples 1-10 in which a portion of the surface of the high nickel positive electrode material is coated with lithium boron oxide and another portion of the surface of the high nickel positive electrode material has a higher first coulombic efficiency, a significantly higher capacity retention rate after 100 cycles, a significantly lower initial impedance, and a significantly lower impedance growth rate. In particular, by comparing Examples 1 and 5-10 in which the conditions in Steps S1-S2 are exactly the same with Comparative Example 3, it can be seen that, compared with Comparative Example 3 in which there is no lithium boron oxide and fluoride on the surface of the high nickel positive electrode material, the battery in Examples 1 and 5-10 in which a portion of the surface of the high nickel positive electrode material is coated with lithium boron oxide and another portion of the surface of the high nickel positive electrode material has a higher first coulombic efficiency, a significantly higher capacity retention rate after 100 cycles, a significantly lower initial impedance, and a significantly lower impedance growth rate.
[0101] By comparing the results of Examples 1-10 with Comparative Example 4, it can be seen that compared with Comparative Example 4 in which the high-nickel positive electrode material has not been treated with step S1, step S2, step S3 and step S4, the battery in Examples 1-10, which has been washed and coated with lithium boron oxide on a portion of the surface of the high-nickel positive electrode material and has fluoride in point form on another portion of the surface of the high-nickel positive electrode material, has a higher first coulombic efficiency, a significantly higher capacity retention rate after 100 cycles, a significantly lower initial impedance and a significantly lower impedance growth rate, and the positive electrode composite material in Examples 1-10 has a lower residual lithium content.
[0102] It can be seen from the above battery performance test results that the positive electrode composite material of the present invention, the method for preparing the positive electrode composite material, and the positive electrode and lithium-ion secondary battery containing the positive electrode composite material can effectively reduce the amount of residual lithium, inhibit the side reaction between the positive electrode composite material and the electrolyte in the lithium-ion secondary battery, improve the first coulombic efficiency of the lithium-ion secondary battery, improve the cycle performance of the lithium-ion secondary battery and reduce the impedance growth of the lithium-ion secondary battery.
[0103] The above description is only the preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A positive electrode composite material, characterized in that: The positive electrode composite material comprises: High nickel cathode material; Lithium boron oxide covering a portion of the surface of the high nickel positive electrode material; and The fluoride exists in the form of dots on another part of the surface of the high nickel positive electrode material. The residual lithium content on the surface of the positive electrode composite material is less than 0.3 wt %.
2. The positive electrode composite material according to claim 1, characterized in that: The lithium boron oxide uniformly covers the surface of the secondary particles and the grain boundaries of the primary particles of the high-nickel positive electrode material.
3. The positive electrode composite material according to claim 1, characterized in that: The lithium boron oxide includes one or more of LiBO2, Li3BO3, Li2B4O7, Li2B2O4 and Li3B3O6.
4. The positive electrode composite material according to claim 1, characterized in that: The fluoride includes LiF.
5. The positive electrode composite material according to claim 4, characterized in that: The fluoride further comprises one or more of MgF2, AlF3, NH4F, MnF4, TiF3, ZrF4, SrF3 and MoF5.
6. The positive electrode composite material according to claim 1, characterized in that: The high nickel cathode material has the general formula LiNi x Co y M 1-x-y O2, where 0.6≤x≤1, 0≤y<0.4, and M is Mn, Al, Mg, Ti, Fe, Cu, Zn, One or more of Ga, Zr, Mo, Nb and W.
7. The positive electrode composite material according to claim 1, characterized in that: The amount of boron element in the positive electrode composite material is in the range of 0.01 wt % to 0.50 wt %.
8. The positive electrode composite material according to claim 1, characterized in that: The amount of fluorine element in the positive electrode composite material is in the range of 0.01 wt % to 1.00 wt %.
9. A method for preparing a positive electrode composite material, characterized in that: The method comprises: Step S1: mixing a high-nickel positive electrode material with water or a solution formed by an acid and a non-aqueous solvent to obtain a first mixture; Step S2: filtering the first mixture to obtain a filtered product, and then vacuum drying, grinding and sieving the filtered product to obtain a washed product; Step S3: mixing the washed product with a boron-containing compound and a fluoride by ball milling to obtain a second mixture; and Step S4: sintering the second mixture to obtain the positive electrode composite material.
10. The method for preparing a positive electrode composite material according to claim 9, characterized in that: In step S1, the acid includes an organic acid, an inorganic acid or a mixture thereof. Preferably, the organic acid includes one or more of maleic acid, acrylic acid, fumaric acid, malonic acid, oxalic acid, malic acid, glycolic acid, succinic acid, citric acid, trisaccharic acid and aconitic acid. Preferably, the inorganic acid includes one or both of phosphoric acid and silicic acid.
11. The method for preparing a positive electrode composite material according to claim 9, characterized in that: In the step S1, the non-aqueous solvent includes an alcohol solvent. Preferably, the alcohol solvent includes one or more of methanol, ethanol, isopropanol, ethylene glycol and glycerol.
12. The method for preparing a positive electrode composite material according to claim 9, characterized in that: In the step S2, the vacuum drying is performed at a temperature in the range of 60°C-150°C, and the vacuum drying time is in the range of 0.1h-12h.
13. The method for preparing a positive electrode composite material according to claim 9, characterized in that: In the step S3, the rotation speed of the ball milling is in the range of 100 rpm-500 rpm, and the time of the ball milling is in the range of 10 min-2 h.
14. The method for preparing a positive electrode composite material according to claim 9, characterized in that: In step S3, the fluoride includes one or more of LiF, MgF2, AlF3, NH4F, MnF4, TiF3, ZrF4, SrF3 and MoF5.
15. The method for preparing a positive electrode composite material according to claim 9, characterized in that: In step S3, the boron-containing compound comprises one or both of boric acid and boron oxide.
16. The method for preparing a positive electrode composite material according to claim 9, characterized in that: In step S4, the sintering temperature is in the range of 200°C-600°C, the sintering time is in the range of 2h-8h, preferably, the heating rate is in the range of 6°C / min-15°C / min, and preferably, the sintering atmosphere is oxygen.
17. A positive electrode for a lithium ion secondary battery, characterized in that: The positive electrode of a lithium-ion secondary battery comprises the positive electrode composite material according to any one of claims 1 to 8.
18. A lithium ion secondary battery, characterized in that: The lithium-ion secondary battery comprises: positive electrode, The negative electrode, and Diaphragm, Characterized in that the positive electrode comprises the positive electrode composite material according to any one of claims 1 to 8.